Moral margins concerning the use of coercion in psychiatry - Landeweer, Elleke GM (Nursing ethics, 2011)
In the closed wards of mental health institutions, moral decisions are made concerning the use of forced seclusion. In this article we focus on how these moral decisions are made and can be improved. We present a case study concerning moral deliberations on the use of seclusion and its prevention among nurses of a closed mental health ward. Moral psychology provides an explanation of how moral judgments are developed through processes of interaction. We will make use of the Social Intuitionist Model of Jonathan Haidt that emphasizes the role of emotions, intuitions and the social context in moral judgments and reasoning. We argue that this model can help to explain social dynamics in the context of enforced seclusion. In the discussion we explore how moral psychology can be complemented with the normative perspective of dialogical ethics to develop strategies for improving psychiatric practices. We conclude that social processes play an important role in moral deliberations and that moral development can be fostered by bringing in new perspectives in the dialogue. Moral case deliberation provides a practical tool to systematically organize moral reflections among nurses on the work floor.